PENINGKATAN HASIL BELAJAR SISWA PADA MATA PELAJARAN MATEMATIKA MENGGUNAKAN MODEL QUANTUM TEACHING - Maharani, Winda (EduHumaniora | Jurnal Pendidikan Dasar Kampus Cibiru, 2017)
Abstract: The problem of this study is the low of the third grade student learning outcomes at Gunung Mekar Elementary School in Mathematics. The results of preliminary observations showed that 58.82% of students have not reached the passing grade and the learning has not been implemented optimally. The aim of this study is for increasing the outcomes of student’s mathematics learning by using Quantum Teaching Model. The kind of this study is a classroom action research, with the data collection’s form is the test sheet. The analysis technique used in this study is a quantitative analysis technique. The results of this study shows that the implementation of Quantum Teaching Model could increase the student’s learning outcomes. The percentage of student’s mastery learning outcomes increased from the first cycle to the second cycle with the percentage of the first cycle is 64.70% (category quite well) and increased to 82.35% (the excellent category) in the second cycle.               Keywords: quantum teaching model, learning outcomes, mathematics Abstrak: Masalah dalam penelitian ini adalah rendahnya hasil belajar siswa kelas III SD Negeri 2  Gunung Mekar pada mata pelajaran matematika. Hasil observasi awal menunjukkan bahwa 58,82% siswa belum mencapai KKM dan pembelajaran belum dilaksanakan secara optimal. Penelitian ini bertujuan untuk meningkatkan hasil belajar matematika siswa dengan menerapkan model quantum teaching. Jenis penelitian ini adalah penelitian tindakan kelas, alat pengumpul data penelitian berupa soal test. Teknik analisis yang digunakan dalam penelitian ini adalah teknik analisis kuantitatif. Hasil penelitian menunjukkan bahwa penerapan model quantum teaching pada pembelajaran matematika dapat meningkatkan hasil belajar siswa. Persentase ketuntasan hasil belajar siswa meningkat dari siklus I ke siklus II dengan persentase siklus I sebesar 64.70% (kategori cukup baik) dan meningkat menjadi 82.35% (kategori sangat baik) pada siklus II.Kata kunci: model quantum teaching, hasil belajar, matematika